Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1101/2021.05.30.445673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prioritization of autoimmune disease-associated genetic variants that perturb regulatory element activity in T cells

Abstract: Genome-wide association studies have uncovered hundreds of autoimmune disease-associated loci; however, the causal genetic variant(s) within each locus are mostly unknown. Here, we perform high-throughput allele-specific reporter assays to prioritize disease-associated variants for five autoimmune diseases. By examining variants that both promote allele-specific reporter expression and are located in accessible chromatin, we identify 60 putatively causal variants that enrich for statistically fine-mapped varia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 81 publications
0
0
0
Order By: Relevance
“…Because of linkage disequilibrium (LD) between variants, multiple variants in a region may show statistically significant associations even if only one has a true functional effect, and the lead variant may not always be a causal variant. Adding to this complexity, recent massively parallel reporter assay (MPRA)-based studies have suggested that many associated loci (estimates range from 17% to 40% of tested loci) may have multiple functional variants in high LD (65,66). Statistical fine-mapping approaches attempt to address the issue of LD by assigning a causal probability to the lead variant of the association or by narrowing the potential causal variants to a small set, although they cannot differentiate between multiple putatively causal variants in high LD.…”
Section: Prioritizing Causal Variants Statistical Fine-mappingmentioning
confidence: 99%
“…Because of linkage disequilibrium (LD) between variants, multiple variants in a region may show statistically significant associations even if only one has a true functional effect, and the lead variant may not always be a causal variant. Adding to this complexity, recent massively parallel reporter assay (MPRA)-based studies have suggested that many associated loci (estimates range from 17% to 40% of tested loci) may have multiple functional variants in high LD (65,66). Statistical fine-mapping approaches attempt to address the issue of LD by assigning a causal probability to the lead variant of the association or by narrowing the potential causal variants to a small set, although they cannot differentiate between multiple putatively causal variants in high LD.…”
Section: Prioritizing Causal Variants Statistical Fine-mappingmentioning
confidence: 99%